1997
DOI: 10.1007/s004970050080
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of tubulin from ginkgo pollen

Abstract: Tubulin was purified by a combination of acetone powder preparation, DEAE Sephadex A-50 chromatography, Sephacryl S-300 gel filtration, and Mono Q anion exchange chromatography from the pollen of ginkgo (Ginkgo biloba L.), a typical gymnosperm. The average yield of tubulin is 2 mg per 100 g of pollen grain. The purified tubulin is electrophoretically homogeneous. It seems to be composed of two subunits on SDS-PAGE and is resolved as two major spots on two-dimensional electrophoresis, preliminarily indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Previous biochemical studies have shown that tubulin from Ginkgo pollen has similar properties to that in animal and other plant cells (Zhang et al 1997). Now, microtubules have also been found to be distributed along the longitudinal axis, extending to the tip in Ginkgo pollen tubes, which is similar to previous reports regarding the distribution of microtubules in P. abies.…”
Section: Figs 1-6supporting
confidence: 89%
“…Previous biochemical studies have shown that tubulin from Ginkgo pollen has similar properties to that in animal and other plant cells (Zhang et al 1997). Now, microtubules have also been found to be distributed along the longitudinal axis, extending to the tip in Ginkgo pollen tubes, which is similar to previous reports regarding the distribution of microtubules in P. abies.…”
Section: Figs 1-6supporting
confidence: 89%
“…This process typically yielded 2.0 mg of and 1.3 mg of pure tubulin from 1 liter of culture. The procedure proved to be efficient, as reported from other sources such as tubulin from ginkgo pollen, 2 mg from 100 gm of ginkgo pollen, 7) and Mimosa pudica, 1.5 mg from 50 g leaves. 6) Even though decreasing the temperature has been successful in reducing the tendency of certain proteins to aggregate, 32,33) in this case, the content of soluble protein remained unchanged at different induction times (6-15 h), growth phases, and through a temperature range of 30 to 18 C (data not shown).…”
Section: Analysis Of and Tubulin Sequencessupporting
confidence: 63%
“…This structure resembled previously published normal microtubular structures from other plant sources in terms of appearance and size. 6,7) The correct and efficient refolding of an inclusion body to its active form has been a topic in both basic research and industrial applications. This method gave = tubulin in correctly folded form since recombinant tubulins formed heterodimers and polymerized to microtubule like structures.…”
Section: Polymerization Of Tubulinmentioning
confidence: 99%
See 1 more Smart Citation
“…• C. Tubulin from apple pollen was purified according to the literature [24]. Apple pollen (1 g) was germinated as described above and homogenized in 5 ml of lysis buffer 2 containing 50 mM Pipes, pH 6.8, 2 mM MgCl 2 , 2 mM EGTA, 1 mM DTT, plant protease inhibitor cocktail from Sigma and 0.1 mM GTP.…”
Section: Purification Of Actin From Apple Pollenmentioning
confidence: 99%